Application of modern theories to comprehend the concepts of the knowledge economy and National Innovation System : Chapter of the monograph ﻿ - Kalaman, Olga В.; Каламан, Ольга Борисівна; Каламан, О. Б.; Mandrykin, Denys (Poznan : Wydawnictwo Naukowe Akademii Nauk Stosowanych im. Ksiecia Mieszka I w Poznaniu, 2022)
The task of the study is to scientifically comprehend the concepts of the knowledge econ- omy and National Innovation System (NIS), which resulted in the formation of new theoretical and analytical approaches to the study of these aspects. The study considers the theoretical knowledge economy concept, and, in particular, shows its differences from the industrial econ- omy through the definition of the main characteristics at the macro and micro levels. The key role played by knowledge in new economy sectors was also identified, and the knowledge role in the process of creating value in the economy was analyzed. The main means and mechanisms for a successful transition to the knowledge economy were identified. As a result, we found that the role of the state is considered central in the transi- tion to the knowledge economy through innovation policies and strategies designed to take into account economic and social aspects in the transition process. The stages of development of the NIS concept were analyzed, and the fundamental differ- ence between the NIS and the knowledge economy was established. We found that the knowl- edge economy is a broader category than the NIS and has a broader geographical coverage, including diversified economic activities. In addition, a number of factors and principles were proposed that play an important role in the formation and development of the NIS, its adaptation to the requirements of the process of transition to the knowledge economy. In addition to the analysis and modeling of the dynamics of functional interaction between the subjects of the national innovation system. In addition, the theoretical significance of the study lies in the development of methods for assessing and analyzing the effectiveness of national innovation systems, as well as in building an institutional framework for regulating interaction between NIS entities in different contexts. This, in turn, will help future researchers understand how both the knowledge economy and the NIS work. There are many characteristics that distinguish the knowledge economy from traditional forms of the economy, which explores the nature of production relations, productive forces and means of production. Thus, in the context of the knowledge economy, a new direction of political economy has emerged, in which various economic and social components operate.
Kalaman O. Application of modern theories to comprehend the concepts of the knowledge economy and National Innovation System / O. Kalaman, D. Mandrykin // Knowledge management: seven effective examples of applying knowledge : Scientific monograph / Scientific Editor Walery Okulicz-Kozaryn. - Poznan : Wydawnictwo Naukowe Akademii Nauk Stosowanych im. Ksiecia Mieszka I w Poznaniu.- 2022.- Р. 9-47
Keywords: knowledge; knowledge economy; innovation system; national innovation system; disseminating knowledge; innovation system development; знання; економіка знань; інноваційна система; національна інноваційна система; поширення знань; розвиток інноваційної системи; Research Subject Categories::SOCIAL SCIENCES::Business and economics